2003
DOI: 10.1021/jm020854p
|View full text |Cite
|
Sign up to set email alerts
|

New Lupane Derived Compounds with Pro-Apoptotic Activity in Cancer Cells:  Synthesis and Structure−Activity Relationships

Abstract: Cellular screening of various synthetic triterpenoid compounds formally derived from lupane has identified a number of analogues as potential anticancer drug candidates. Here we describe the synthesis and structure-activity relationships of betulin and betulinic acid derivatives containing an E-ring modified with different oxygen functions. Thus compounds containing the lup-18-en-21-one, lup-18-ene-21,22-dione, 18,19-secolupane, and the highly oxygenated 18,19-secolupane systems, as well as des-E-lupane deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…In a previous study, we demonstrated that BA was cytotoxic to an MDR erythroleukemia cell line that overexpresses ABCB1 (24). The antitumoral effect of BA was also observed in tumor cell lines with defective or mutated p53 (13,16), as well as in cell lines that acquire resistance to cytotoxic drugs (16,18). In this study, we investigated the effect of BA on Ma-104, a non-tumoral renal cell line that constitutively expresses P-gp/ABCB1 and MRP1/ABCC1 (20).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In a previous study, we demonstrated that BA was cytotoxic to an MDR erythroleukemia cell line that overexpresses ABCB1 (24). The antitumoral effect of BA was also observed in tumor cell lines with defective or mutated p53 (13,16), as well as in cell lines that acquire resistance to cytotoxic drugs (16,18). In this study, we investigated the effect of BA on Ma-104, a non-tumoral renal cell line that constitutively expresses P-gp/ABCB1 and MRP1/ABCC1 (20).…”
Section: Resultsmentioning
confidence: 89%
“…1, BA decreased the viability of Ma-104 cells in a dose-dependent manner. High concentrations of BA were required to substantially decrease the viability of Ma-104 cells after 48 h of treatment; however, at 10 μg/ml, a concentration at which BA is highly cytotoxic (14)(15)(16)(17)(18)(19), the effect of BA on Ma-104 was very low. Thus, to avoid the possible interference of cell death mechanisms on the measurement of ABCB1 and ABCC1 activities, subsequent experiments were performed using 10 μg/ml of BA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…for biological activity and found that they demonstrated significant cytotoxic 172 activity under in vitro conditions (Table 2). Roseotoxins also have strong anti-inflammatory activity 173 (Table 3) in vitro.…”
Section: Biological Activities Of Cyclic Peptidesmentioning
confidence: 99%
“…1), including medulloblastoma, glioblastoma, Ewing's sarcoma (23), neuroblastoma (24) and leukemia (25). BA has been demonstrated to be effective on drug-resistant and -sensitive tumor cell lines, indicating its significant therapeutic benefit to chemotherapy-resistant patients with cancer (26). In addition, the impact of BA on hedgehog signalling was determined, which has been implicated in rhabdomyosarcoma development (27).…”
Section: Introductionmentioning
confidence: 99%